Characteristic Analysis of Commercial Wound Dressings - KRISHNA PRASAD, G.; RAJA, A. S. M.; SENTHILKUMAR, T.; VIGNESHWARAN, N.; PATIL, P. G. (Cotton Research Journal, 2021)
In the current decade, the use of textile-based high-performance wound dressing is growing due to the demand for quick healing from the trauma, in-situ drug delivery and other functional requirements. Today different types of wound dressing materials are manufactured for different types of dressing i.e. primary, secondary, occlusive and semi-occlusive dressing. In this study, most commonly available wound dressings were evaluated and compared in vitro. Standard test methods were employed during the study to determine the absorbency, dehydration rate, mass loss (%) of dressing. It was found that the cotton non-woven based wound dressing had better absorbency than the synthetic or foam-based dressings.